Spatiotemporal Dynamics and Driving Mechanisms of Cropland Ecosystem Health in the Black Soil Region of Northeast China - Yuxin Yang; Guoqiang Yu; Xin Wang; Jiping Liu (Sustainability, 2026)
Understanding the spatiotemporal dynamics and driving mechanisms of cultivated land ecosystem health in the Northeast black soil region is essential for sustainable land management, regional ecological security, and national food security. This study selected 2002, 2012, and 2022 as representative years. Based on CLCD land use data and related natural and socio-economic datasets, an evaluation framework was established incorporating comprehensive productivity, landscape stability, and ecological sustainability. The cultivated land ecosystem health index (FEHI) was calculated using an integrated evaluation framework combining the InVEST model and weighted evaluation method, and the spatial differentiation characteristics and driving mechanisms were investigated using the GeoDetector model. The results showed that (1) among the three study years, cultivated land comprehensive productivity generally increased, whereas landscape stability declined and ecological sustainability remained at a relatively low level with signs of degradation; (2) the FEHI exhibited a fluctuating upward pattern, with the mean value increasing from 0.195 to 0.211. Low-health areas decreased, while high-health areas expanded, suggesting an enhancement in the comprehensive health level of cultivated land ecosystems. (3) GeoDetector analysis revealed that precipitation and elevation were the dominant factors influencing spatial differentiation. The interactions between precipitation and slope, as well as precipitation and nighttime light intensity, showed strong explanatory power, although the explanatory power of dominant factors varied among different years. These findings provide scientific support for ecological protection, black soil conservation, and sustainable cultivated land management in the Northeast black soil region.